2018
DOI: 10.1007/s10856-018-6077-x
|View full text |Cite
|
Sign up to set email alerts
|

An oxygen plasma treated poly(dimethylsiloxane) bioscaffold coated with polydopamine for stem cell therapy

Abstract: In this study, 3D macroporous bioscaffolds were developed from poly(dimethylsiloxane) (PDMS) which is inert, biocompatible, non-biodegradable, retrievable and easily manufactured at low cost. PDMS bioscaffolds were synthesized using a solvent casting and particulate leaching (SCPL) technique and exhibited a macroporous interconnected architecture with 86 ± 3% porosity and 300 ± 100 μm pore size. As PDMS intrinsically has a hydrophobic surface, mainly due to the existence of methyl groups, its surface was modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…The chambers in this group had the highest wettability, highest O proportion, and lowest C proportion among all the chambers, and all the differences were statistically significant. The O proportion result indicated that the Si(-O 2 ) peak was much higher for the PN chambers compared with the other types; a hydrophilic silica-like layer had formed on the PDMS surface, which resulted in high wettability (Razavi & Thakor, 2018). The result that the lowest C proportion was in the PN chambers indicated that the methyl groups initially on the external surface of the chambers had moved to the internal surfaces (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The chambers in this group had the highest wettability, highest O proportion, and lowest C proportion among all the chambers, and all the differences were statistically significant. The O proportion result indicated that the Si(-O 2 ) peak was much higher for the PN chambers compared with the other types; a hydrophilic silica-like layer had formed on the PDMS surface, which resulted in high wettability (Razavi & Thakor, 2018). The result that the lowest C proportion was in the PN chambers indicated that the methyl groups initially on the external surface of the chambers had moved to the internal surfaces (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have found that cells seeded on top of these materials will attach and proliferate normally ( Schaffer et al, 1994 ). Furthermore, these silicone membranes can foster both viability and proliferation of seeded ASCs ( Razavi and Thakor, 2018 ). The ability to treat and coat silicone and other biomaterials remains an attractive method to promote differentiation and growth, and these parameters may be tuned to optimize proper cell growth.…”
Section: Cell Delivery Methodsmentioning
confidence: 99%
“…The chambers in this group had the highest wettability, highest O proportion, and lowest C proportion among all the chambers, and all the differences were statistically significant. The O proportion result indicated that the Si(-O 2 ) peak was much higher for the PN chambers compared with the other types; a hydrophilic silica-like layer had formed on the PDMS surface, which resulted in high wettability (Razavi & Thakor 2018). The result that the lowest C proportion was in the PN chambers indicated that the methyl groups initially on the external surface of the chambers had moved to the internal surfaces (Figure 4).…”
Section: Physical and Chemical Basis For The Good Cellular Proliferatmentioning
confidence: 98%